IMPLEMENTASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN TEMATIK KELAS III SDIT DARUL HASAN PADANGSIDIMPUAN - Asriana Harahap (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
This study aims to describe the implementation of character values ​​in thematic learning, the character values ​​developed and to find out the supporting factors and inhibiting factors for the implementation of character values ​​in thematic learning for class III SDIT Darul Hasan Padangsidimpuan. This research uses a qualitative approach with a descriptive type. The research subjects were class III students and homeroom teachers and school principals to support the data. This research was conducted at SDIT Darul Hasan Padangsidimpuan in the odd semester of the 2017/2018 school year. Data collection techniques used by observation, interviews and documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. Data validity technique with source and technique triangulation. The results of the research show that the implementation of character values ​​includes planning and implementation. The lesson plan consists of a syllabus from the department/government and lesson plans made by the teacher himself. Meanwhile, in practice, the teacher implements character values ​​through learning activities and learning methods, assessment, instilling discipline, habituation and exemplary. The character values ​​developed by the teacher in thematic learning are obtained from character values ​​that often appear, other character values ​​that rarely appear. Supporting factors in the implementation of character values ​​are schools through activities and facilities, teachers through example, learning strategies, media and learning resources. Inhibiting factors are the environment, students and time.